Development and verification of a 281-group WIMS-D library based on ENDF/B-VII.1. (May 2016) - Dong, Zhengyun; Wu, Jun; Ma, Xubo; Yu, Hui; Chen, Yixue
Highlights: A new WIMS-D library based on SHEM 281 energy structures is developed. The method for calculating the lambda factor is illustrated and parameters are discussed. The results show the improvements of this library compared with other libraries. Abstract: The WIMS-D library based on WIMS 69 or XMAS 172 energy group structures is widely used in thermal reactor research. Otherwise, the resonance overlap effect is not taken into account in the two energy group structure, which limits the accuracy of resonance treatment. The SHEM 281 group structure is designed by the French to avoid the resonance overlap effect. In this study, a new WIMS-D library with SHEM 281 mesh is developed by using the NJOY nuclear data processing system based on the latest Evaluated Nuclear Data Library ENDF/B-VII.1. The parameters such as the thermal cut-off energy and lambda factor that depend on group structure are discussed. The lambda factor is calculated by Neutron Resonance Spectrum Calculation System and the effect of this factor is analyzed. The new library is verified through the analysis of various criticality benchmarks by using DRAGON code. The values of multiplication factor are consistent with the experiment data and the results also are improved in comparison with other WIMS libraries.